Observation of Center Disaster Damage on Pariaman and Wasior Using Differential Sar Interferometry (Dinsar) - Sudiana, Dodi; Rizkinia, Mia (Makara Journal of Technology, 2012)
This study focuses on disaster observations in Pariaman (West Sumatera) and Wasior (Papua) using remote sensing techniques (differential SAR interferometry). Differential interferometry (DInSAR) method was performed on two PALSAR data sets with different acquisition months, i.e. about a month after and before disaster, respectively. The center damage of Pariaman earthquake and Wasior flood can be determined by deriving Land Subsidence using DInSAR method.